Editorial Vol15 no2 - Laura Steckley (Scottish Journal of Residential Child Care)
Welcome to the September 2016 issue of the Scottish Journal of Residential Child Care. We have another great mix of informative and thought-provoking writing from near and far for your perusal. In our previous two issues, we included a thread of information, discussion and debate about the Named Person scheme. There have been further related developments here in Scotland and my first order of business is to revisit this thread. In our December, 2015 issue, we included opinion pieces by Mike Burns and Maggie Mellon arguing for and against the scheme. In our April 2016 issue, Joint Editor Graham Connelly offered further information about the scheme, including an account of the subsequent appeal that was being considered. We also included correspondence from Hazel Whitters and Tracey Jarvis in response to the opinion pieces in the December issue.